Epidemiological characteristics and spatial analysis of leprosy cases in an endemic municipality - Mateus Santos de Jesus; Teovan Andrade Sandes; Ana Caroline Rodrigues Lima; Katyucia Oliveira Crispim de Souza; José Augusto Passos Góes; Allan Dantas dos Santos (Universidade Federal do Ceará, 2019)
Objective: to analyze the epidemiological characteristics and spatial distribution of leprosy cases in an endemic municipality. Methods: epidemiological, retrospective study with spatial analysis techniques developed with data from the National System of Compulsory Notification. Leprosy cases were georeferenced using a Geographic Positioning System receiver for the spatial location of the households. Spatial analysis was performed by the Kernel method. Results: one hundred new cases of leprosy were reported, and there was predominance of males and patients with low education. The Virchowian clinical form was predominant (32.0%) and 48.0% of the cases presented some degree of disability at the time of diagnosis. There was an increasing temporal trend in the detection rate. The spatial analysis identified critical areas for occurrence of leprosy, which was concentrated in the urban area (71.0%). Conclusion: the municipality presented high endemicity for leprosy, with heterogeneous distribution of cases and risk cluster in the urban area.